2020
DOI: 10.2147/cmar.s237582
|View full text |Cite
|
Sign up to set email alerts
|

<p>WD Repeat Domain 5 Promotes Invasion, Metastasis and Tumor Growth in Glioma Through Up-Regulated Zinc Finger E-Box Binding Homeobox 1 Expression</p>

Abstract: Background: Glioma is one of the important diseases that threaten human survival in today's society. WD repeat domain 5 (WDR5) belongs to the components of the lysine methyltransferase complex. WDR5 is involved in gene transcription regulation, cell senescence, cancer and other biological events through methylation modification. However, its expression and function in glioma are still unclear. Materials and Methods: The expression of WDR5 was observed in glioma cells, and then a glioma cell line SW1783 knocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The correlation between WDR5 and metastasis has been hinted at in breast cancer, glioma, and colon cancer, by participating in several signaling pathways such as transforming growth factor (TGF)-b signaling and the phosphatidylinositol 3-kinase (PI3K)/AKT pathway. 16,56,57 For the first time, we linked WDR5 with HIF-1a and its downstream TWIST1 and suggested that WDR5 resulted in metastasis by promoting HIF-1a-induced EMT. This conclusion enhanced current understanding of WDR5 as an oncoprotein, especially in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between WDR5 and metastasis has been hinted at in breast cancer, glioma, and colon cancer, by participating in several signaling pathways such as transforming growth factor (TGF)-b signaling and the phosphatidylinositol 3-kinase (PI3K)/AKT pathway. 16,56,57 For the first time, we linked WDR5 with HIF-1a and its downstream TWIST1 and suggested that WDR5 resulted in metastasis by promoting HIF-1a-induced EMT. This conclusion enhanced current understanding of WDR5 as an oncoprotein, especially in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that WDR5 mediates self-renewal in embryonic stem cells by regulating the OCT4-SOX2-NANOG pluripotency transcription factor network (Ang et al, 2011). While WDR5 has been documented to be expressed in GBM and neuroblastoma and functionally important in high-passage GBM models (Dai et al, 2020; Wang et al, 2020), WDR5 function has not been investigated in the cancer stem cell state in GBM or in GBM organoid culture, and therapeutic inhibition of WDR5 has not been tested in GBM.…”
Section: Resultsmentioning
confidence: 99%
“…While WDR5 has been documented to be expressed in GBM and neuroblastoma and functionally important in high-passage GBM models (Dai et al, 2020;Wang et al, 2020), WDR5 function has not been investigated in the cancer stem cell state in GBM or in GBM organoid culture, and therapeutic inhibition of WDR5 has not been tested in GBM.…”
Section: Spatially Resolved Organoid Screening Reveals Wdr5 Is Essent...mentioning
confidence: 99%
“…Besides, USP44 and WDR5 are also associated with the metastasis of cancer, such as the migration and invasion capability of cancer cells and vasculogenic mimicry [12,13,27,[36][37][38]. WDR5 is also related to the liver infiltration of leukemia cells [23].…”
Section: Discussionmentioning
confidence: 99%